Drainage Pattern Recognition Method Using Graph Convolutional Networks Combined With Three‐Dimensional Elevation Features - Qiang, Bo; Liu, Tao; Du, Ping; Li, Pengpeng; Wang, Wenning; Xu, Shenglu (Transactions in GIS, 2025)
ABSTRACT Drainage pattern recognition plays a crucial role in flood management, hydraulic engineering site selection, and biodiversity maintenance. Although deep learning methods have been widely employed in drainage pattern recognition in recent years, most research has focused on two‐dimensional features, with limited attention given to the impact of three‐dimensional elevation features. This study, therefore, introduces a graph convolutional network (GCN) approach that incorporates three‐dimensional elevation features. This method integrates three‐dimensional elevation features into the feature system of deep learning‐based drainage pattern recognition for the first time, combining two‐dimensional geometric and topological features to comprehensively capture variations in both vertical and planar morphology of drainage patterns. Specifically, this study extracts representative drainage pattern samples (e.g., dendritic, skeleton, parallel, and fan) from OSM and HydroSHEDS river vector data. Six features are designed based on the micro‐to‐macro processes involved in drainage pattern development, and a novel drainage pattern feature description index is proposed. A GCN model architecture based on the first‐order Chebyshev polynomial is then developed to extract both global and local information of drainage patterns under three‐dimensional elevation features. Experimental results demonstrate that the recognition accuracy of this method achieves 90% on the test dataset, with precision, recall, and F1 scores improving by at least 3% compared to methods such as support vector machines (SVM) and GraphSAGE. This suggests that the feature description index incorporating three‐dimensional elevation features more comprehensively reflects the development process of drainage patterns, thereby improving recognition accuracy and offering new methods and perspectives for drainage pattern research.